The potential of the Green Bond markets in Latin America and the Caribbean (2020)
The publication of this study is part of the EU-LAC Foundation’s continued commitment to supporting the partnership agenda between Europe, Latin America and the Caribbean involving the participation and inputs from civil society and other social actors. One of the areas of priority for the bi-regional strategic partnership is addressing climate change. The countries of both regions have been the driving force of and have adopted the Paris Agreement on Climate Change, as well as the Sustainable Development Goals (SDGs). The revised chapter 2 of the EU-CELAC Action Plan (Brussels, 2018) indicates the need for “the optimization and scaling up of existing and upcoming networks and programmes in Latin America and in the Caribbean, taking advantage of the opportunities offered by investment facilities, as appropriate. In addition, promote triangular cooperation to leverage the contributions of other actors and resources, as well as innovative sources and mechanisms of additional financing”. To effectively combat climate change, it is urgent and necessary to fund mitigation and adaptation efforts at various levels. In recent years, green bonds have increasingly stood out as a funding instrument for green projects that contribute to tackling climate change. The success of the green bond market to raise capital for the implementation of the 2030 agenda is stimulating strong interest in a growing number of countries to develop national green bond frameworks that link international good practice to local priorities. In this context, based on a study carried out by the European Commission in 2016 on the development and functioning of the green bonds market in Europe, the EU-LAC Foundation launched in 2019 a call for a study on the potential of the green bonds market in Latin America and the Caribbean, including comparative aspects with the European market. The consortium of researchers selected by the call was led by EAFIT University and had the participation of Hill Consulting and Get2C. The study presented in this publication analyses the incentives and barriers for the expansion of the green bond market in LAC. To this end, 4 case studies were deepened to exploring aspects related to the regulatory framework and governance structures, standards, accountability, policies and programmes, actors and sectors. The report also presents a set of recommendations. This publication is timely as 2020 marks the beginning of a decade of urgent action on climate and sustainability where the role of the financial sector will be crucial. The EU-LAC Foundation would like to thank Ernesto Jeger, Programme Manager of Sustainable Development and Economic Issues, who coordinated this project from the Foundation.